PENINGKATAN KETERAMPILAN BERPIKIR KREATIF SISWA MELALUI MODEL PROJECT BASED LEARNING BERBANTUAN MIND MAP KREATIF PADA MATERI TEATER RAKYAT - Hafidz Ibnu Ruhanis, Ahmad Al; Aliya Ruhanis, Naja; Trisakti Handayani; Nur Faridah; Fakhintan Ilza Karengga; Yasmin Tiara Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Creative thinking skills in the 21st century are a crucial competency for every student. However, data from observations and interviews indicate that some students still struggle to develop creative ideas, lack confidence in expressing their thoughts, and tend to simply follow provided examples. Additionally, students face difficulties distinguishing between types of folk theater based on their characteristics. This study aims to enhance students' creative thinking skills regarding folk theater through the Project-Based Learning (PjBL) model supported by creative mind maps. The study employed the Kemmis & McTaggart Classroom Action Research (CAR) model, conducted over two cycles comprising planning, implementation, observation, and reflection stages. Data were collected via observation, interviews, and documentation, then analyzed using both quantitative and qualitative descriptive methods. The results show: (1) an improvement in students' creative thinking skills, rising from 50.93% in the pre-cycle stage to 63.53% in Cycle I, and further to 82.22% in Cycle II. These findings demonstrate that the PjBL model supported by creative mind maps is effective in enhancing students' creative thinking skills. Future research could explore applying this model to other arts and culture topics and at different educational levels.